(untitled) (Philological Studies, 2020)
The paper analyses substantive derivatives in the local variety of Ter/Pradielis, part of the Tersko dialect of Slovene, from a synchronic-diachronic point of view and from the point of view of language contact. The corpus of analysed lexemes comprises of 989 derived and non-derived substantives, recorded between 2013 and 2018. Substantive derivatives are analysed according to their suffixes, motivating lexemes, and derivational meaning. A stronger emphasis is given to synchronically derived lexemes, while synchronically non-derived lexemes are considered to a lesser extent. Those derivational meanings and suffixes that can be assumed to have arisen or been induced by language contact with neighbouring Romance idioms are also analysed contrastively, especially in regard to their functioning in Friulian.